2013
DOI: 10.1614/ws-d-12-00065.1
|View full text |Cite
|
Sign up to set email alerts
|

Competition between ACCase-Inhibitor Resistant and Susceptible Sterile Wild Oat (Avena sterilis) Biotypes

Abstract: Studies were conducted to determine the growth, fecundity, and competitive ability of an acetyl-CoA carboxylase (ACCase)–inhibitor resistant (R) sterile wild oat biotype compared with a susceptible (S) biotype. Seed germination studies indicated that there were no differences in seed germination and seedling vigor between R and S biotypes at any temperature regime. R and S biotypes were grown under noncompetitive and competitive arrangement in the greenhouse. Under noncompetitive greenhouse conditions, growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…It has to be noted that the resistant accession was found in the area near susceptible accessions. Such an observation is in agreement with the findings of previous studies for other weed species [21,26]. Even if the field history was not known for all sites, conversation with growers from the orchards and vineyards with the resistance issues provided history of continuous glufosinate use at twoto fourtimes higher than the labeled rate.…”
Section: Preliminary Screeningsupporting
confidence: 91%
“…It has to be noted that the resistant accession was found in the area near susceptible accessions. Such an observation is in agreement with the findings of previous studies for other weed species [21,26]. Even if the field history was not known for all sites, conversation with growers from the orchards and vineyards with the resistance issues provided history of continuous glufosinate use at twoto fourtimes higher than the labeled rate.…”
Section: Preliminary Screeningsupporting
confidence: 91%
“…Previous studies on several weeds have shown either higher seed production for R compared with the S population (Purrington and Bergelson, 1997;Park et al, 2004), or no differences at all between the several biotypes (Alcocer-Ruthling et al, 1992; Thompson et al, 1994;Travlos, 2013).…”
Section: Growth Of R and S Populations Under Non-competitive Conditiomentioning
confidence: 94%
“…Some resistant biotypes of rigid ryegrass were also shown to be more competitive in terms of seed size compared to the susceptible population (Pedersen et al, 2007). Travlos (2013) showed that there were not any significant fitness differences between ACCase-inhibitor FIGURE 1 | Star (*) and R rating system to distinguish the degree of resistance, according to the response to a single dose of herbicide in resistance screening (Moss et al, 1999). The numbers in parentheses represent the standard errors of the means.…”
Section: Introductionmentioning
confidence: 99%
“…It possess an important economic menace to crop yields, because of their high spread germination and great degree of phenotypic differentiation, essential generative produce and in the absence of competition, A. sterilis being considered to produce large number of seeds, and ability of seed to remain in the soil seed bank [1][2][3]. Sterile wild oat has been found in Mediterranean climate zone, such as Southern Europe and Northern Africa [4].…”
Section: Introduction mentioning
confidence: 99%